Przywództwo – ustalenia definicyjne i sposoby rozumienia - Cybal-Michalska, Agnieszka (Wydawnictwo Naukowe UAM, 2015)
This article picks up a few threads that focus on the subject of leadership, as well as on the possibilities of its empirical verification or implication in practice. In the last four decades it has been noticed that there are more and more various concurrent theoretical assumptions about leadership. The Author emphasises that the value of a debate about the leadership career theory is determined by the critical way of looking at the multiplicity of theoretical perspectives. The Author points to the fact that there is a need to generate new attitudes so that they are relevant to the dynamics of the modern world changes, as well as to challenges of effective leadership. The conceptual complexity of the leadership phenomenon and its multidimensionality, multidirectionality, flexibility and contextualism determine the need to integrate the multiplicity of positions and theoretical orientations.
Leadership – Attempts of Definition and Ways of Perception
Keywords: leadership; leadership process; leadership features; leadership rules